The Effect of Hand Grip Training on Increasing the Speed of Rock Climbers in UKM Garjamara - Aditya Nugraha; Dewi Susilawati; Rizal Ahmad Fauzi (Universitas Negeri Semarang, 2026)
This study aims to determine the effect of hand grip training on increasing rock climbing speed in members of the Garjamara student activity unit. The research method used is quantitative research with a pre-experimental design using a one group pretest-posttest design. The population in this study amounted to 30 members of the Garjamara Student Activity Unit, while the research sample was 10 people who were selected using the purposive sampling technique based on certain criteria. The research instrument uses a rock climbing speed test that has met the requirements for validity and reliability. Data analysis techniques in-clude descriptive statistics and paired sample T-test to determine the difference in results before and after treatment. The results showed that the average pre-test score of The results showed that the participants' average climbing time de-creased from 4.4130 seconds in the pretest to 2.9170 seconds in the posttest. This decrease in climbing time indicates an increase in climbing speed after handgrip training, which showed an increase in rock climbing speed after being given hand grip training. The results of the paired sample t-test obtained a significance value of 0.000 (<0.05) with a calculated t-value of -9.849, thus showing that there is a significant influence of hand grip training on increasing rock climbing speed. The increase occurred because hand grip exercises were able to increase hand grip strength, arm muscle endurance, and movement efficiency when climbing. Thus, hand grip training can be used as one of the effective physical training methods to improve the performance of rock climbing athletes, especially in speed climbing.